SIMBOLISME DALAM TRADISI LISAN PASANG RI KAJANG: TINJAUAN SEMIOTIK - Basrah Gising (Fakultas Sastra Universitas Negeri Malang, 2012)
Semiotics is a set of analysis that has been applied in linguistics and anthropology. This article is focused on language and cultural symbols that are stated in pasang ri Kajang and will be analyzed based on grand theory of semantics.This research used a qualitative research perspective. The validity of data is examined by collecting the data collecting through interview, recording, taking note, elicitation and Focus Group Study. The result of the research indicates that Pasang ri Kajang contains a holy ancestor messages that has been transferred in oral tradition. These messages contain some local wisdoms of sustainable environmental management. The topic of this research is local knowledge system that concerns with hydraulic cycle system that is stated in some matters of pasang ri Kajang. The relationship between the matters build a substantial concept that concerns with hydraulic cycle system in ecology.